Analysis of Sales Level Through the Cost of Promotion in Gas 15 Coffee and Friends Ciputat Restaurant in Tangerang Selatan City - Juhaeri, Juhaeri; Paeno, Paeno; Ahidin, Udin; Kautsarzafira, Kautsarzafira (PINISI Discretion Review, 2019)
Responding to intense competition, companies must have a competitive strategy. No matter how good a product is if consumers are not notified, then the product will not be purchased by consumers. The main purpose of this study was to determine the costs incurred, to determine sales, and to determine the effect of promotional costs on sales at Gas15 Coffee And Friend Restaurant in Ciputat, South Tangerang City. The research method used in this research is a quantitative descriptive and quantitative associative approach with the verification approach. The method of collection is by observing, studying documentation and studying literature. The analytical method used is the Simple Linear Regression Test, Product Moment Correlation Test, Determination Test, and Hypothesis Test (t-test). The data is then processed using the Statistical Social Science (SPSS) version 23.00. The results of this study indicate that the promotion costs incurred during the past five years have increased. Sales over the past five years have fluctuated. There is a very strong positive influence and promotion costs on sales at Gas15 Coffee And Friend Restaurant in Ciputat, South Tangerang City